2014
DOI: 10.1105/tpc.114.124883
|View full text |Cite
|
Sign up to set email alerts
|

HEAT-INDUCED TAS1 TARGET1Mediates Thermotolerance via HEAT STRESS TRANSCRIPTION FACTOR A1a–Directed Pathways inArabidopsis   

Abstract: Many heat stress transcription factors (Hsfs) and heat shock proteins (Hsps) have been identified to play important roles in the heat tolerance of plants. However, many of the key factors mediating the heat response pathways remain unknown. Here, we report that two genes, which are targets of TAS1 (trans-acting siRNA precursor 1)-derived small interfering RNAs that we named HEAT-INDUCED TAS1 TARGET1 (HTT1) and HTT2, are involved in thermotolerance. Microarray analysis revealed that the HTT1 and HTT2 genes were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
127
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(128 citation statements)
references
References 75 publications
(112 reference statements)
1
127
0
Order By: Relevance
“…Overexpression of PPR40 / At3g16890 enhanced salinity tolerance in Arabidopsis (Zsigmond et al 2012). Similarly, TAS1 -ta-siRNA targets, At4g29760 , At4g29770 , and At5g18040 (designated as Heat Induced TAS1 Target genes, HTT4 , HTT1 and HTT2 , respectively), were responsive to heat stress and downregulation of these targets reduced heat tolerance in Arabidopsis (Li et al 2014). Of these targets, At4g29760 and At5g18040 , along with another potential TAS1 -ta-siRNA target, At1g51670 , also showed contrasting expression levels compared to TAS1 originating ta-siRNAs in response to cold stress (Kume et al 2010).…”
Section: Mirna and Stress Regulation Mechanismsmentioning
confidence: 99%
“…Overexpression of PPR40 / At3g16890 enhanced salinity tolerance in Arabidopsis (Zsigmond et al 2012). Similarly, TAS1 -ta-siRNA targets, At4g29760 , At4g29770 , and At5g18040 (designated as Heat Induced TAS1 Target genes, HTT4 , HTT1 and HTT2 , respectively), were responsive to heat stress and downregulation of these targets reduced heat tolerance in Arabidopsis (Li et al 2014). Of these targets, At4g29760 and At5g18040 , along with another potential TAS1 -ta-siRNA target, At1g51670 , also showed contrasting expression levels compared to TAS1 originating ta-siRNAs in response to cold stress (Kume et al 2010).…”
Section: Mirna and Stress Regulation Mechanismsmentioning
confidence: 99%
“…It was also found that HTT1 interacted with the heat shock proteins HSP70‐14 and HSP40 in Arabidopsis . These results suggest that HTT1 mediates thermotolerance pathways targeted by TAS1a , mainly activated by HSFA1a , and acts as cofactor of HSP70‐14 complexes (Li et al ; Figure ).…”
Section: The Associations Between Sirnas Other Small Rnas and Tempermentioning
confidence: 94%
“…Plant genomes also encode a unique class of sRNAs called trans‐acting small interfering RNAs (ta‐siRNAs) which exert their functions through posttranscriptional gene silencing (Li et al ). In Arabidopsis , there are four families of noncoding precursor genes generating ta‐siRNA: trans‐acting siRNA precursor 1 ( TAS1) , TAS2 , TAS3 and TAS4 .…”
Section: The Associations Between Sirnas Other Small Rnas and Tempermentioning
confidence: 99%
See 1 more Smart Citation
“…The repression of target genes by miRNAs may be especially suited to integrate stress responses over time, as, in the case of translational inhibition, the repression is reversible and a degradation of the miRNA will quickly relieve the block on translation. Other small RNAs (miR398, TAS1) were recently implicated in the acquisition of thermotolerance, 31,32 however, it remains to be tested whether they also play a role in heat stress memory.…”
mentioning
confidence: 99%